A Study on the Students’ Understanding in Guessing Synonym Word at the Eighth Grade Students of SMP Negeri 2 Mandau (LPPM STMIK Dharmapala Riau, 2022)
This paper entitled “A Study on the Students’ Understanding in Guessing Synonym Word of the Eighth Grade Students at SMP Negeri 2 Mandau”. The research is a descriptive research, intended to know students understanding in guessing synonym word of the eighth grade students at SMP Negeri 2 Mandau. The subject of this research is the eighth grade student of SMP Negeri 2 Mandau. The object of this research is the students understanding in guessing synonym word. The population of this research is the eighth grade student of SMP Negeri 2 Mandau. There is eight class of population. Total numbers of students are 320.The researcher uses the Simple Random Sampling. From eighth classes, the researcher takes two random classes as sample. The sample is class VIII.1 and VIII.2. Total of the sample is 80 students. The result of this research showed that students understanding in guessing synonym word of the eighth grade students at SMP Negeri 2 Mandau falls to good level. This can be seen on the results of the test conducted by the researcher. The researcher got the total score of the whole students is 5600. So, the average score of the students is 70. Based on the score above, students understanding in guessing synonym word of the eighth grade students at SMP Negeri 2 Mandau falls to good level.